WADY WRODZONEThymus macroscopic findings in a child with congenital heart disease: the role of intraoperative evaluation in histiocytosis diagnosis - Jaworski, Radosław; Haponiuk, Ireneusz; Irga, Ninela; Chojnicki, Maciej; Zieliński, Jacek; Steffek, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
We present a case report of a 20-month-old girl with secundum atrial septal defect referred for cardiac surgery with histiocytosis of the thymus diagnosed on the basis of histopathological examination of intraoperatively resected thymus. Immediate diagnosis of multiorgan histiocytosis remains extremely important for successful therapy, any delay of chemotherapy usually results in poor prognosis. In conclusions, we emphasize the role of histopathological examination in any unclear or atypical macroscopic thymus image.